Teacher nonverbal cues and student first impressions in Vietnamese EFL classrooms - Phan, Quoc Cuong; Manao, Angelica Puspasari (English Language Teaching Educational Journal, 2025)
This study explores the perspectives of Vietnamese students on nonverbal cues from their English teachers and how these cues influence their first impressions and motivation in EFL classrooms. Using an explanatory sequential mixed-methods design, the study first collected survey data from 97 students across four majors (Information Technology, Law, Marketing, and Public Relations) and then conducted semi-structured interviews with 12 voluntary participants. Quantitative results indicated consistently positive evaluations of nonverbal cues, particularly confident posture, neat attire, and smiling, with notable differences between majors: students in communication-oriented fields placed greater value on visual and interpersonal cues, while technical students adopted more neutral stances and frequently compared English teachers with instructors in their major subjects. Thematic analysis of interview data further revealed that nonverbal cues from teachers contributed to lowering anxiety, enhancing classroom inclusion, and increasing student engagement. In general, the study highlights the significant role of nonverbal communication of teachers in creating supportive and motivating EFL learning environments and provides pedagogical implications for improving teacher training and classroom interaction in Vietnamese universities.